2008
DOI: 10.1080/00365510802126844
|View full text |Cite
|
Sign up to set email alerts
|

Acute variation of biochemical markers of muscle damage following a 21‐km, half‐marathon run

Abstract: The results suggest the hypothesis that sub-maximal exercise influences the concentration of several biomarkers of muscle damage for up to 24 h with no biochemical signs of myocardial damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
2
17

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 24 publications
4
60
2
17
Order By: Relevance
“…In contrast to the findings of the current study the literature review suggest that exercise increases SGPT values (Fathi & Majid, 2015;Foran, Lewandrowski, & Kratz, 2003;Joksimovic et al, 2015;Kim, Lee, & Kim, 2007;Lippi et al, 2008) as well as SGOT values (Foran, Lewandrowski, & Kratz, 2003;Kim, Lee, & Kim, 2007;Lippi et al, 2008). These differences are probably affected by the duration and the intensity of training (Buchheit, Voss, Nybo, Mohr, & Racinais, 2011;Hurley et al, 1995).…”
Section: Enzymescontrasting
confidence: 99%
“…In contrast to the findings of the current study the literature review suggest that exercise increases SGPT values (Fathi & Majid, 2015;Foran, Lewandrowski, & Kratz, 2003;Joksimovic et al, 2015;Kim, Lee, & Kim, 2007;Lippi et al, 2008) as well as SGOT values (Foran, Lewandrowski, & Kratz, 2003;Kim, Lee, & Kim, 2007;Lippi et al, 2008). These differences are probably affected by the duration and the intensity of training (Buchheit, Voss, Nybo, Mohr, & Racinais, 2011;Hurley et al, 1995).…”
Section: Enzymescontrasting
confidence: 99%
“…The evaluation of total LDH and its isoenzymes allows obtaining much information about the muscle metabolism [4]. In fact strenuous exercise induces a significant increase of LDH [31] and the degree of the rise depends on the intensity and duration of the effort [32,33]. We did not found an increase of total enzyme in Group A, neither in Group B, in both tests (C and H), probably for the type and intensity of effort: In our study the time of examination (30 minutes after exercise) and the type of exercise (submaximal) did not allow to detect a significant increase of total enzyme (Tables 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…Lippi et al 15 found in their study variations of AST (positive and significant) that accompanied the changes in CK and LDH proportionally, characterizing these markers as efficient in identifying physical damage from overload, on condition that measured are combined. Thus, such 16 , this is justified because the depletion of the anaerobic pathway (ATP-CP) fibers II (intermediate) and R (resistance) occurs through a continuous endurance exercise and subsequent activation of aerobic metabolism by the glycolytic pathway.…”
Section: Discussionmentioning
confidence: 98%